Transformasi UMKM Desa Kraton menjadi Industri Halal yang Kompetitif melalui Pendampingan Sertifikasi Halal - Kalamillah, Achmad Muqtafin; Muttaqin, Zainal; Prayoga, Galang Eka; Ardiwijaya, Candra; Aziz, Moh. Mahaizaz Syifa Alwi; Wafa, Muhammad Athoila; Khusna, Fitria Asmaul; Azizah, Alfina Dewi Nur; Ariyanti, Shikita Dina; Muthoharoh, Roihatul; Hasanah, Sri Rahayu Nur; Khasanah, Ulil Afidatul; Mufidah, Aisya; Sefia, Putri Ilma; Arkya, Kaela; Safitri, Julian Dwi; Sari, Septia Nanda; Khasanah, Ri’anatul; Firdaus, Zahraini Jannatul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
This community service activity aims to transform MSMEs in Kraton Village into a competitive halal industry through halal certification assistance. The background to this activity is based on the importance of halal certification in increasing consumer confidence and product competitiveness in local and global markets. Many MSMEs in Kraton Village do not understand the procedures and benefits of halal certification, so educational and mentoring interventions are needed. The implementation method includes an outreach stage to increase MSME players' understanding of the urgency of halal certification, technical training related to administrative requirements and halal product standards, as well as assistance in the certification application process to relevant institutions. The results of the activity show an increase in MSME actors' understanding of the halal concept, their skills in fulfilling certification requirements, as well as achieving halal certification for several superior MSME products. This activity is expected to encourage the growth of halal MSMEs in Kraton Village and increase their competitiveness in the market.